Paracingulate Sulcus Length Is Shorter in Voice-Hearers Regardless of Need for Care. (20th May 2020) - Powers, Albert R; van Dyck, Laura I; Garrison, Jane R; Corlett, Philip R
Abstract: Hallucinations—while often considered an indication of mental illness—are commonly experienced by those without a need for clinical care. These nonclinical voice-hearers offer an opportunity to investigate hallucinations in the absence of confounds inherent to the clinical state. Recent work demonstrates an association between auditory verbal hallucinations (AVH) and structural variability in paracingulate sulcus (PCS) of medial prefrontal cortex in a clinical population. However, before PCS length may be considered a biomarker for clinical hallucination risk, it is necessary to investigate PCS structure in a nonclinical population of voice-hearers with AVH phenomenology similar to those of their clinical counterparts. In the current study, PCS length was measured from T1-weighted structural MRI scans of four groups of participants: (1) voice-hearers with a psychotic disorder (n = 15); (2) voice-hearers without a psychotic disorder (n = 15); (3) nonvoice-hearers with a psychotic disorder (n = 14); and (4) nonvoice-hearers without a psychotic disorder (n = 15). There was a main effect of AVH status—but not psychosis—on right PCS length, with no interaction of AVH and psychosis. Participants with AVH exhibited reduced right PCS length compared to participants without AVH (mean reduction = 8.8 mm, P < 0.05). While past studies have demonstrated decreased PCS length in clinical voice-hearers, ours is the first demonstration that shorter right PCS extends to nonclinical voice-hearers. Our findings support the hypothesis that differences in PCS length are related to the propensity to hear voices and not to illness, consistent with a continuum model of voice-hearing.